The European Union and the new Latin American integration: comparison parameters applied in different studies on the integration processes - Leví Coral, Michel (2011)
The author maintains that the usual procedure of comparing experiments of integration tends to be misleading, because those analyses usually ignore the social, political and institutional differences among the countries that make up a region. The author examines the literature produced since 2000 that analyses Latin American experiments with integration in light of the European experience. He concludes that this comparison suffers from serious methodological and theoretical problems.